PENGARUH TERPAAN KONTEN KINDERFLIX DAN KREDIBILITAS HOST NISA DI CHANNEL KINDERFLIX TERHADAP PERILAKU BERKOMENTAR CYBER SEXUAL HARASSMENT PENONTON DEWASA DI KONTEN KINDERFLIX - Sabila Rosyad, Ananda; Lukmantoro, Triyono; Qurrota Ayun, Primada (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Women often become victims of sexual objectification on social media or online. One of them is Nisa who is the host of the Kinderflix channel which brings educational content for toddlers. Even though Nisa wears a hijab and dresses modestly, she receives many harassing comments on the Kinderflix content she presents. This research aims to determine whether there is an influence between exposure to Kinderflix content and the credibility of host Nisa on the Kinderflix channel regarding the behavior of commenting on cyber sexual harassment of adult viewers on Kinderflix content. This research has an explanatory type and the theories used are uses & gratifications theory and source credibility theory. The research test uses a simple linear regression test with a non-probability sampling technique. The sample used in this research was 60 respondents with criteria aged 17-35 years, users of social media Instagram, Youtube and TikTok, and had been exposed to Kinderflix content. The results of this research show that exposure to Kinderflix content on cyber sexual harassment commenting behavior has a significant influence, so the hypothesis is accepted because the result value is 0.001 or smaller than 0.01. Exposure to Kinderflix content has an influence of .27.4% on cyber sexual harassment commenting behavior. Then, the results of host Nisa's credibility test regarding cyber sexual harassment commenting behavior are very significant or influential because the result value is 0.001 and is smaller than 0.01. Nisa's host credibility has an influence of 21.2% on cyber sexual harassment commenting behavior